Blowin’ in the Nonisothermal Wind: Core-powered Mass Loss with Hydrodynamic Radiative Transfer - William Misener; Matthäus Schulik; Hilke E. Schlichting; James E. Owen (The Astrophysical Journal)
The mass loss rates of planets undergoing core-powered escape are usually modeled using an isothermal Parker-type wind at the equilibrium temperature, T _eq . However, the upper atmospheres of sub-Neptunes may not be isothermal if there are significant differences between the opacity to incident visible and outgoing infrared radiation. We model bolometrically driven escape using AIOLOS, a hydrodynamic radiative-transfer code that incorporates double-gray opacities, to investigate the process’s dependence on the visible-to-infrared opacity ratio, γ . For a value of γ  ≈ 1, we find that the resulting mass loss rates are well approximated by a Parker-type wind with an isothermal temperature T  =  T _eq /2 ^1/4 . However, we show that over a range of physically plausible values of γ , the mass loss rates can vary by orders of magnitude, ranging from 10 ^−5 ×  the isothermal rate for low γ to 10 ^5 ×  the isothermal rate for high γ . The differences in mass loss rates are largest for small planet radii, while for large planet radii, mass loss rates become nearly independent of γ and approach the isothermal approximation. We incorporate these opacity-dependent mass loss rates into a self-consistent planetary mass and energy evolution model and show that lower/higher γ values lead to more/less hydrogen being retained after core-powered mass loss. In some cases, the choice of opacities determines whether or not a planet can retain a significant primordial hydrogen atmosphere. The dependence of escape rate on the opacity ratio may allow atmospheric escape observations to directly constrain a planet's opacities and therefore its atmospheric composition.